Do Experiences of Success and Failure Influence Beliefs about Inequality? Evidence from Selective University Admission. (June 2023) - Wetter, Rebecca; Finger, Claudia
Previous research suggests that beliefs about inequality are often biased in ways that serve people's own interests. By contrast, people might uphold system-justifying beliefs, such as meritocratic beliefs. We test these assumptions against real-life experience of highly selective university admission. Using panel data on German medical school applicants allows us to measure belief changes through experiences of success or failure in admission. We find support that self-serving bias in beliefs outweighs the motivation for system justification: success strengthens the belief that admission depends on effort, while failure reinforces the belief that admission depends on luck. These patterns partly manifest themselves in beliefs about societal inequality. Additionally, we argue that previous experiences (long-term experiences of social upbringing and short-term experiences in university admissions) provide a frame for new experiences, examine respective effect heterogeneity, and discuss implications of our findings of diverging paths in inequality beliefs of winners and losers for the persistence of inequality.